Poorly differentiated XX/XY sex chromosomes are widely shared across skink radiation - Kostmann, Alexander; Kratochvíl, Lukáš; Rovatsos, Michail (Proceedings. Biological sciences, 2021)
Differentiated sex chromosomes are believed to be evolutionarily stable, while poorly differentiated sex chromosomes are considered to be prone to turnovers. With around 1700 currently known species forming ca 15% of reptile species diversity, skinks (family Scincidae) are a very diverse group of squamates known for their large ecological and morphological variability. Skinks generally have poorly differentiated and cytogenetically indistinguishable sex chromosomes, and their sex determination was suggested to be highly variable. Here, we determined X-linked genes in the common sandfish (Scincus scincus) and demonstrate that skinks have shared the same homologous XX/XY sex chromosomes across their wide phylogenetic spectrum for at least 85 million years, approaching the age of the highly differentiated ZZ/ZW sex chromosomes of birds and advanced snakes. Skinks thus demonstrate that even poorly differentiated sex chromosomes can be evolutionarily stable. The conservation of sex chromosomes across skinks allows us to introduce the first molecular sexing method widely applicable in this group.
Keywords: ještěři; Sex Determination Processes; genome; zvířata; sex chromosomes; molecular sexing; Snakes; vertebrates; Phylogeny; analýza určování pohlaví; Lizards; Sex Chromosomes; pohlavní chromozomy; hadi; Animals; sex determination; procesy určující pohlaví; Sex Determination Analysis; qPCR; fylogeneze